Predictors of transcatheter closure cancellation in children with ventricular septal defect - Artha Christin Yulianti; Indah Kartika Murni; Noormanto Noormanto; Sasmito Nugroho (Paediatrica Indonesiana, 2021)
Background Ventricle septal defect (VSD) is the most common type of congenital heart disease in children. If definitive therapy delayed, failure to thrive and developmental delays can lead to decreased quality of life. The options for VSD closure include surgical and minimally invasive procedures with transcatheterization. Although transcatheterization is considered to be the safest therapy, the risk of complications can lead to cancellation of procedure. Objective To determine whether nutritional status, body height, VSD type and size, and type of device used were predictors of cancellation of transcatheter closure of VSD. Methods A retrospective cohort study using medical records was performed for all children who underwent transcatheter closure of VSD at Dr. Sardjito Hospital, Yogyakarta, Central Java, between January 2017 to March 2020. Cancellation of closure was defined as complications occurring during the procedure, such as cardiac conduction problems, valve regurgitation, and device embolization. Multivariate logistic regression analysis was done to determine independent predictors of closure cancellation. Results One hundred thirty-four children were enrolled. Independent variables that were significant predictors were doubly committed subarterial (DCSA) VSD type (OR 5.98; 95%CI 1.52 to 23.61; P=0.045), moderate VSD size (OR 15.59; 95%CI 4.67 to 52.06; P=0.001), and types of devices used: symmetric (OR 27.06; 95%CI 2.75 to 266.17; P=0.001), asymmetric (OR 16.46; 95%CI 2.15 to 210.0; P=0.001), and coil (OR 21.26; 95%CI 2.15 to 210.0; P=0.001). Taller body height was a protective factor against cancellation of the procedure (OR 0.98; 95%CI 0.96 to 1.00; P=0.008). Conclusion Significant predictors of cancellation of transcatheter VSD closure are DCSA VSD, moderate VSD size, as well as coil, symmetric, and asymmetric devices, and increased body height.